La Cofradía de Nuestra Señora del Rosario de Andacollo: Antecedentes de su formación y evolución histórica (siglos XVII al XVIII) - Cordero Fernández, Macarena (Cauriensia, 2023)
The purpose of this article is inform the formation and development of the Brotherhood of Nuestra Señora del Rosario de Andacollo, a mining settlement of the Corregimiento de La Serena (Kingdom of Chile), which had a great regional projection, which allowed the gestation of a space for religious, social, cultural and racial integration between the various subjects that made it up, with a view to unveil the devotional and popular practices of the confreres, such as the questions that were raised against them from the Church for their distance from sound doctrine. In turn, highlight the role of the Dominicans in its organization and the dispute between this religious order and the Bishopric of Santiago de Chile, due to the absence of ecclesiastical authorization that this corporation maintained for a long time.